Association between apical periodontitis and brain inflammation: a systematic review from animals and human studies - da Conceição Francisquini, Julia; Toro, Luan Felipe; Azevedo, Renato Gomes; Tessarin, Gestter Willian Lattari [UNESP] (Springer Nature, 2025)
Apical periodontitis (AP) is an oral inflammatory disease induced by dental pulp infection. It is characterized by inflammation, destruction, and resorption of mineralized tissues located around the dental apex. Although this is a local infection, pathogens and their products in the periapical area, as well as inflammatory cytokines, can reach other regions of the body and trigger a systemic immune/inflammatory response in the host. This condition has been associated with several types of systemic diseases. This systematic review aimed to explore the association between AP and neuroinflammation, providing insights into this relationship and discussing potential pathways used by AP microorganisms to reach the central nervous system. Extensive searches in electronic databases (PubMed, Embase, and Cochrane) and hand searches were conducted from January 2013 until May 2024, using the keywords apical periodontitis, endodontic infection, periapical abscess, periodontitis apical, brain inflammation, brain disorders, and neuroinflammation. Initially, 394 studies were selected. After exclusion and inclusion criteria were applied, 12 studies (7 case reports and 1 case series, 3 experimental studies using animal models, and 1 cohort study) were included in this systematic review. All studies showed the presence of AP in upper and/or lower teeth and brain disorders with neuroinflammation. It is important to mention that some cases reported the death of the patient. This systematic review indicates a significant relationship between AP and neuroinflammation based on animal and human studies. Moreover, this study suggests there may be pathways connecting upper and lower teeth with apical periodontitis to the brain, inducing neuroinflammation. Additionally, the oral cavity can become easily accessible when AP is present, allowing for the invasion of microorganisms that are usually non-invasive. This contributes to the development of systemic disorders and/or strengthens their effect, worsening brain pathologies by causing or enhancing neuroinflammation, potentially leading to death. Based on these inferences, periapex health care is essential to improve the health of the world population. Registration number: Prospero registration nº. CRD42023453543.
Keywords: Apical periodontitis; Central nervous system; Inflammation; Neuroinflammation; Systematic review